Aglomerasi Ekonomi dan Total Faktor Produktivitas Industri Manufaktur di Pulau Jawa - ., Gosen; Susanti, Hera (Jurnal Kebijakan Ekonomi, 2019)
This study discusses the effect of economic agglomeration on the productivity of manufacturing industry companies by using case studies on the island of Java which is the location of more than 80 percent of large and medium industrial companies in Indonesia. The company productivity used in this study is the total factor productivity (TFP) with the economic agglomeration variable used is localization economies, urbanization economies, and competition. The results showed that agglomeration in the form of urbanization economies had a positive and significant effect on the total growth of company productivity factors, whereas agglomeration in the form of localization economies had a negative effect. Increased business competition due to the company's spatial concentration also has a positive impact on productivity. Thus, spatial concentration in the form of industrial diversity and improving conditions of business competition in the district / city area have a positive impact on increasing the scale of the company's production and need to be considered in the industrial regional policy making process. Keywords: Manufacturing, total factor productivity, economic agglomeration